2013
DOI: 10.1038/onc.2012.609
|View full text |Cite
|
Sign up to set email alerts
|

Ink4a/Arf−/− and HRAS(G12V) transform mouse mammary cells into triple-negative breast cancer containing tumorigenic CD49f− quiescent cells

Abstract: Intratumoral heterogeneity within individual breast tumors is a well-known phenomenon that may contribute to drug resistance. This heterogeneity is dependent on several factors, such as types of oncogenic drivers and tumor precursor cells. The purpose of our study was to engineer a mouse mammary tumor model with intratumoral heterogeneity by using defined genetic perturbations. To achieve this, we used mice with knockout (−/−) of Ink4a/Arf, a tumor suppressor locus; these mice are known to be susceptible to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We previously showed that H‐Ras G12V transforms Ink4a/Arf knockout C57BL/6 mouse mammary gland cells and thereby established a syngeneic mouse model of triple‐negative breast cancer (TNBC) (Kai et al . ). In the present study, we set out to establish malignant mesenchymal tumor models through the expression of H‐Ras G12V in wild‐type mouse mammary gland cells.…”
Section: Resultsmentioning
confidence: 97%
“…We previously showed that H‐Ras G12V transforms Ink4a/Arf knockout C57BL/6 mouse mammary gland cells and thereby established a syngeneic mouse model of triple‐negative breast cancer (TNBC) (Kai et al . ). In the present study, we set out to establish malignant mesenchymal tumor models through the expression of H‐Ras G12V in wild‐type mouse mammary gland cells.…”
Section: Resultsmentioning
confidence: 97%
“…We previously showed in TNBC and glioblastoma multiforme mouse models that cancer stem cells (CSCs) have a quiescent trait and overexpress IGF-I, which was a key molecule for making CSCs quiescent in these models (20, 24). On the basis of these findings, we assumed that letting CSCs exit from the quiescent state and stay in mitosis by inhibiting IGF-IR and Aurora A/B may work as CSC-targeted therapy in TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…In each experiment, DMSO-treated cells were used as the control. Cell-cycle distribution was analyzed by a fluorescence-activated cell sorter (FACS) as described previously (19, 20). For mitotic analysis, cells were stained with anti-phospho-histone H3 (pHisH3) conjugated with FITC, incubated with RNase (100 μg/mL), and stained with PI (25 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the differences caused by the loss of Llgl1 and the different populations that are observed, we evaluated the cells using breast cancer stem cell markers CD44, CD49f, and CD24 [25][26][27][28][29]. Analysis of the parental MCF12A and shControl transduced cells revealed a consistent CD44 lo /CD49f hi /CD24 hi phenotype (data not shown and Figure 2A and 2C).…”
Section: Llgl1 Regulates Expression Of Cell Lineage Markersmentioning
confidence: 99%
“…Characteristics that define these cells include serial transplantation in vitro and in vivo, and the expression of a variety of surface markers, including CD44 hi /CD24 lo , CD44 hi , and CD49f lo , among others [25][26][27][28][29]. Of note, TAZ nuclear translocation is known to potentiate EGFR signaling pathways, which in turn can increase CD44 transcription and stem cell characteristics [30,31].…”
Section: Introductionmentioning
confidence: 99%